1994
DOI: 10.1111/j.1365-2265.1994.tb02556.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum insulin‐like growth factor I in a random population sample of men and women: relation to age, sex, smoking habits, coffee consumption and physical activity, blood pressure and concentrations of plasma lipids, fibrinogen, parathyroid hormone and osteocalcin

Abstract: The present data can be used as reference values for IGF-I (at least in Caucasians) for the diagnosis of growth hormone disturbances and as guidelines for growth hormone substitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
201
8
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(239 citation statements)
references
References 35 publications
28
201
8
2
Order By: Relevance
“…During puberty, however, IGF-I levels are higher in girls than in boys, even when corrected for Tanner stages (13). In young adults, IGF-I levels are higher in females, but in mid-life adult men display higher IGF-I levels (10,14). These differences are believed mainly to depend on the GH status, which subsequently may be influenced by sex hormones.…”
Section: Discussionmentioning
confidence: 91%
“…During puberty, however, IGF-I levels are higher in girls than in boys, even when corrected for Tanner stages (13). In young adults, IGF-I levels are higher in females, but in mid-life adult men display higher IGF-I levels (10,14). These differences are believed mainly to depend on the GH status, which subsequently may be influenced by sex hormones.…”
Section: Discussionmentioning
confidence: 91%
“…but have generally similar serum IGF-I levels [3,4]. As expected, female with GH deficiency need a higher dose of GH than male to maintain normal serum IGF-I levels [5,6].…”
mentioning
confidence: 86%
“…Studies among healthy adults have reported a null association (2-4), a positive association (5), an inverse association (6)(7)(8)(9), and a nonlinear association (10,11) between BMI and IGF-I levels. The nonlinear associations were similar to what we observed in Japanese Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, however, have been inconsistent with respect to the relationships between adiposity and circulating levels of IGF proteins (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Studies among healthy adults have reported a null association (2-4), a positive association (5), an inverse association (6)(7)(8)(9), and a nonlinear association (10,11) between body mass index (BMI) and IGF-I levels. We are unaware of any study that has looked at possible ethnic differences in the relationship between obesity and circulating IGF-I, and this may be important in addressing the metabolic basis for ethnic differences in cancer risk.…”
Section: Introductionmentioning
confidence: 98%